Effect of maize-soybean intercropping on soil respiration (Bangladesh Journal of Botany, 2025)
Adopting appropriate cropping systems is an effective way to reduce greenhouse gas (GHG) emission, meanwhile GHG emission from farmland is a hot topic recently. In recent years, maize–soybean intercropping has been promoted in many regions in China. To explore the effects of maize-soybean intercropping on soil CO2 emission and carbon balance, we established three planting methods, namely, maize monoculture (M), soybean monoculture (S), and maize-soybean intercropping (MS). Results showed that the cumulative emissions of soil CO2 were M (21231 kg·hm-2) > S (19715 kg·hm-2) > MS (17321 kg·hm-2). The two-factor composite model of soil temperature and moisture content could explain the variation in soil CO2 emission rate well, which reached 58.36–68.54%. Correlation analysis showed that the soil CO2 emission rate was significantly correlated with peroxidase activity (P＜0.01). The soil carbon balance was favorable under different treatments, serving as a sink for atmospheric carbon. The soil carbon sequestration potential of M and MS treatments was significantly higher than that of S treatment (P